2020
DOI: 10.1016/j.msea.2019.138639
|View full text |Cite
|
Sign up to set email alerts
|

Strength-ductility trade-off via SiC nanoparticle dispersion in A356 aluminium matrix

Abstract: A process was developed to disperse β-SiC nanoparticles (NPs), with a high propensity to agglomerate, within a matrix of A356 aluminum alloy. A suitable dispersion of 1 wt.% SiC NPs in the A356 matrix was obtained through a hybrid process including a solid-state modification on the surface of the NPs, a two-step stirring process in the semi-solid and then the liquid-state, and a final hot-rolling process for fragmentation of the brittle eutectic silicon phase and porosity elimination. Titanium and nickel where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…A process to disperse silicon carbide nano‐particles within aluminium‐silicon7‐magnesium/aluminium alloy matrix was developed. Substantial enhancement in the mechanical properties was observed in the nickel surface modification composites [11].…”
Section: Introductionmentioning
confidence: 95%
“…A process to disperse silicon carbide nano‐particles within aluminium‐silicon7‐magnesium/aluminium alloy matrix was developed. Substantial enhancement in the mechanical properties was observed in the nickel surface modification composites [11].…”
Section: Introductionmentioning
confidence: 95%
“…To be specific on A356 alloy considerable amount work has been carried out to study the influence of various nanosize reinforcing phases such as TiB 2 , Al 2 O 3 , Si 3 N 4 , SiC, MgO, ZrO 2 , carbon nanofibers and carbon nanotubes on mechanical and tribological properties [18][19][20][21][22][23]. Mousavian et al [24] reported development of Ni and Ti surface modified SiC reinforced A356 composites using hot rolling process. The nanocomposite with 3% SiC content showed highest tensile strength of 380 MPa and this enhancement in strength was attributed to Orowan strengthening mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…As for nano particles, they have obvious size effect, thereby drastically improving the strength, plasticity and toughness of AMCs. However, the composites reinforced by nano particles are difficult to be prepare since nano particles are easy to agglomerate, limiting their application scopes [8,9]. In this case, the addition of micron and nano particles simultaneously into AMCs helps to solve the problem of insufficient strength and toughness, which is of great significance to promote the development of lightweight and wear-resistant AMCs [10,11].…”
Section: Introductionmentioning
confidence: 99%